2012
DOI: 10.1063/1.4734018
|View full text |Cite
|
Sign up to set email alerts
|

Branching ratio measurements of the predissociation of 12C16O by time-slice velocity-map ion imaging in the energy region from 108 000 to 110 500 cm−1

Abstract: Direct branching ratio measurements of the three lowest dissociation channels of (12)C(16)O that produce C((3)P) + O((3)P), C((1)D) + O((3)P), and C((3)P) + O((1)D) are reported in the vacuum ultraviolet region from 108,000 cm(-1) (92.59 nm) to 110,500 cm(-1) (90.50 nm) using the time-slice velocity-map ion imaging and nonlinear resonant four-wave mixing techniques. Rotationally, resolved carbon ion yield spectra for both (1)Σ(+) and (1)Π bands of CO in this region have been obtained. Our measurements using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 54 publications
3
38
1
Order By: Relevance
“…13,14 The product branching ratios in the predissociation of CO have been recently measured for the first time using this method in the energy region from 108 000 (13.390 eV) to 110 500 cm −1 (13.700 eV) 15,16 and were found to be strongly dependent on the vibronic states of CO that are excited. In the present study, we are extending these previous branching ratio measurements to the lower energy range from 102 500 (12.709 eV) to 106 300 cm −1 (13.180 eV).…”
Section: Introductionmentioning
confidence: 99%
“…13,14 The product branching ratios in the predissociation of CO have been recently measured for the first time using this method in the energy region from 108 000 (13.390 eV) to 110 500 cm −1 (13.700 eV) 15,16 and were found to be strongly dependent on the vibronic states of CO that are excited. In the present study, we are extending these previous branching ratio measurements to the lower energy range from 102 500 (12.709 eV) to 106 300 cm −1 (13.180 eV).…”
Section: Introductionmentioning
confidence: 99%
“…The VUV induced predissociation of CO(X 1 Σ) leading to the formation of these product channels has not been examined in detail until recently (e.g., Okazaki et al 1998Okazaki et al , 2001Gao et al 2011aGao et al , 2012Gao et al , 2013aGao et al , 2013b. In the past, it was assumed that the ground state channel (4) dominates the photodissociation of CO in the VUV region because formation of the triplet dissociation channels (5) and (6) violates the Wigner electron spin conservation rule.…”
Section: Need For Branching Ratio Measurements Of Vuv Photodissociatimentioning
confidence: 99%
“…In the past, it was assumed that the ground state channel (4) dominates the photodissociation of CO in the VUV region because formation of the triplet dissociation channels (5) and (6) violates the Wigner electron spin conservation rule. Nevertheless, recent studies (Gao et al 2011a(Gao et al , 2012(Gao et al , 2013a(Gao et al , 2013b have reported evidence for the formation of the excited C(…”
Section: Need For Branching Ratio Measurements Of Vuv Photodissociatimentioning
confidence: 99%
See 2 more Smart Citations